(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present study was undertaken to analyze the effect of speed agility and quickness [SAQ] training and circuit training on muscular endurance among hockey players. The investigator has selected N=36 men inter collegiate levelstate level participated hockey players at random from various college of Guntur district of Andhra Pradesh .Their age ranged from 18-25 years. The hockey players chosen for the study were divided into three equal groups n=12 and designated as experimental group ‘A’ experimental group ‘B’ and control group ‘C’. SAQ training were given to group ‘A’ Circuit training were given to group ‘B’ and the ‘CG’ control group ‘C’ were restricted to participate in any activities. The trainings were given for a period of twelve weeks. The data were collected before and after the training by conducting bent knee sit up test. The obtained data’s were analyzed by Analysis of Covariance (ANCOVA). The level of significant was fixed at 0.05 levels. The results of the study showed that SAQ is training and circuit training significantly improved muscular endurance performance of the hockey players when comparative with control group. Circuit training group hockey players shown better performance when comparison with SAQ training group hockey players.